Predictors of quality of life in Czech female breast cancer survivors following treatment with special interest to coping strategies - Jarkovský, Jiří; Skřivanová, Kateřina; Benešová, Klára; Šnajdrová, Lenka; Gregor, Jakub; Peterková, Hana; Bendová, Marcela; Brančíková, Dagmar; Elfmarková, Nela; Svěrák, Tomáš; Anderková, Ľubomíra; Minář, Luboš; et al. (Vnitrni lekarstvi, 2017)
OBJECTIVES: This study examined the prognostic significance of breast cancer patients characteristics (coping strategies, BMI, age) and disease characteristics (stage of disease, relapse) with respect to quality of life (QoL) following treatment.Sample and settings: 120 breast cancer patients following treatment were recruited. Health-related QoL was assessed using the Czech version of FACT-B and SF-36; additionally, we used a life satisfaction questionnaire. Coping strategies were assessed using the SVF-78 method. In our sample of women, the average time from diagnosis to start of the study was 5.3 years. STATISTICAL ANALYSIS: Factors influencing QoL after treatment were analysed with univariate and multivariate linear regression. RESULTS: Overall negative strategy defined in SVF-78 (Flight tendency, Resignation and Self-accusation) was found to be associated with lower scores of most components of used QoL methods, while Resignation was found as the most negatively influencing strategy. Active problem confrontation (Situation control and Positive self-instruction) was associated with better QoL. More advanced stages and recurrence were related to a significant decrease in QoL for certain components only. CONCLUSION: Our findings suggest a significant predictive power of disease-related factors and of patients characteristics including coping strategies for QoL following treatment in Czech breast cancer survivors.Key words: breast cancer survivors - coping strategy - linear regression model - quality of life prediction - resignation.
Keywords: Czech Republic; senioři; senioři nad 80 let; Surveys and Questionnaires; Female; Humans; nádory prsu; lokální recidiva nádoru; lidé; Middle Aged; ženské pohlaví; lidé středního věku; Česká republika; Adaptation, Psychological; průzkumy a dotazníky; Cancer Survivors; kvalita života; Aged, 80 and over; Breast Neoplasms; Quality of Life; dospělí; Adult; Neoplasm Recurrence, Local; adaptace psychologická; přežívající onkologičtí pacienti; Aged